2020
DOI: 10.21062/mft.2020.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of semisolid squeeze casting technology on alpha phase and eutectic of AlSi7Mg0.3

Abstract: The paper deals with processing of material in semisolid state by the technology of semisolid squeeze casting. The investigated material was a subeutectic aluminium alloy AlSi7Mg0.3. The influence of various preparation methods of batch material on the structure after processing by this technology was studied. Alloy AlSi7Mg0.3 was prepared as gravity cast, inoculated, heat treated and by technology of direct squeeze casting. In article is assessed microstructure of castings before and after processing by techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the literature, one can find various theories about what factorinfluences the fragmentation of the structure in castings made with the squeeze casting method. It can be generally stated that the improvement of mechanical properties and the reduction of grain size depends on: undercooling of molten metal, heat transfer coefficient, composition and fraction of forming phases during solidification [4,18]. It should be noted, however, that the mechanical properties and structure of castings produced by squeeze casting as well as by gravity depend on a number of other factors such as the wall thickness of the castings, the geometry of the gate and pouring system, the combination of micro-alloys, modifications, etc [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, one can find various theories about what factorinfluences the fragmentation of the structure in castings made with the squeeze casting method. It can be generally stated that the improvement of mechanical properties and the reduction of grain size depends on: undercooling of molten metal, heat transfer coefficient, composition and fraction of forming phases during solidification [4,18]. It should be noted, however, that the mechanical properties and structure of castings produced by squeeze casting as well as by gravity depend on a number of other factors such as the wall thickness of the castings, the geometry of the gate and pouring system, the combination of micro-alloys, modifications, etc [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In 1966 Thiele and Dunkel showed that the effects of strontium on such alloys are similar and longer-lasting than those of sodium [9]. However, in recent years it has been established that the technological properties of aluminum -silicon alloys can be enhanced by adding modifiers and by applying suitable thermal treatments [10][11][12][13], technological [14], repeated modification [15] and others [16].Mechanical properties of Al-Si cast alloys depend not only on chemical composition but, more importantly, on microstructural features such as morphologies of dendritic α-Al, eutectic Si particles and other intermetallics that present in the microstructure. The porosity of casting alloys also affects their properties [17,18].…”
Section: Introductionmentioning
confidence: 99%